Identifikasi Kesesuaian Lahan Budidaya Tanaman Kelapa Sawit (Elaeis Guineensis Jacq.) Di Gunung Pamela, Serdang Bedagai, Provinsi Sumatera Utara - Desti Kurniawan Gulo (CV. SINAR HOWUHOWU, 2026)
Land suitability evaluation is a crucial stage in sustainable oil palm cultivation development. This study aimed to identify and evaluate land suitability for oil palm (Elaeis guineensis Jacq.) cultivation in Gunung Pamela, Serdang Bedagai Regency, North Sumatra Province. The research was conducted from September to November 2024 using a survey method with a matching approach between land characteristics from laboratory analysis and field observations against oil palm growth requirements based on FAO (1976) criteria. Parameters analyzed included climatic conditions (rainfall, rainy days, temperature), soil physical properties (texture, drainage, effective depth, slope), and soil chemical properties (pH, C-organic, clay CEC, base saturation). Results showed that annual rainfall reached 3,143.8 mm with a water surplus of 1,783.4 mm, 142 rainy days/year, and average temperature of 26.5°C. Soil characteristics indicated clay loam texture, pH 4.5-5.0, C-organic 0.78%, clay CEC 15.8 cmol/kg, base saturation 18.5%, slope 8-16%, and effective depth 75-100 cm. Actual land suitability was classified as S2 (Suitable) with main limiting factors being low pH (nr), slightly impeded drainage (oa), and slope gradient (eh). Potential land suitability can be upgraded to S1 (Highly Suitable) through acid soil amelioration with liming, drainage system improvement, and organic matter addition. This research provides a scientific basis for sustainable land management and oil palm productivity optimization in Gunung Pamela.